Kebutuhan Pelayanan Suportif Pasien Kanker Ginekologi yang Menjalani Terapi - Putri, Riska Hediya; Wahyuni, Diah (Universitas Aisyah Pringsewu (UAP) Lampung, 2019)
The magnitude of the impact cancer has on an individual extends beyond the physical dimension. Evidence shows that aside from the physical impacts, the course of cancer diagnosis and treatments potentially causes psychosocial effects in both the short and long term. Identifying the patient’s need for supportive care, the health care provider can also get a sense of the patient’s expectation for care which he or she has not yet received. This cross-sectional research objective to identify the supportive care needs of the gynecology cancer patients who undergoing therapy. Consecutive sampling technique was performed to select 113 gynecology cancer patients. The results of the research indicated that most of the gynecology cancer patients required that 96 percent of participants stated that their needs for supportive care had caused them a lot of concern, thus needing additional help. Of all supportive care need domains, the highest number of patients reported their needs in the physical domain (82.3 percent). Identifying and facilitating supportive care needs can reduce patient’s distress and improve patient satisfaction and quality of life.